Dopamine D(1) and D(3) Receptors Modulate Heroin-Induced Cognitive Impairment through Opponent Actions in Mice - Zhu, Yongsheng (Int J Neuropsychopharmacol, 2016)
BACKGROUND: Chronic abuse of heroin leads to long-lasting and complicated cognitive impairment. Dopamine receptors are critically involved in the impulsive drug-driven behavior and the altered attention, processing speed, and mental flexibility that are associated with higher relapse rates. However, the effects of the different dopamine receptors and their possible involvement in heroin-induced cognitive impairment remain unclear. METHODS: The 5-choice serial reaction time task was used to investigate the profiles of heroin-induced cognitive impairment in mice. The expression levels of dopamine D(1)- and D(2)-like receptors in the prefrontal cortex, nucleus accumbens, and caudate-putamen were determined. The effects of dopamine receptors on heroin-induced impulsivity in the 5-choice serial reaction time task were examined by agonist/antagonist treatment on D(1) or D(3) receptor mutant mice. RESULTS: Systemic heroin administration influences several variables in the 5-choice serial reaction time task, most notably premature responses, a measure of motor impulsivity. These behavioral impairments are associated with increased D(1) receptor and decreased D(3) receptor mRNA and protein levels in 3 observed brain areas. The heroin-evoked increase in premature responses is mimicked by a D(1) agonist and prevented by a D(1) antagonist or genetic ablation of the D(1) receptor gene. In contrast, a D(3) agonist decreases both basal and heroin-evoked premature responses, while genetic ablation of the D(3) receptor gene results in increased basal and heroin-evoked premature responses. CONCLUSIONS: Heroin-induced impulsive behavior in the 5-choice serial reaction time task is oppositely modulated by D(1) and D(3) receptor activation. The D(1) receptors in the cortical-mesolimbic region play an indispensable role in modulating such behaviors.